2022
DOI: 10.3390/molecules27217411
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Structural Characterization of Two Crystalline Polymorphs of Tafamidis Free Acid

Abstract: Tafamidis, chemical formula C14H7Cl2NO3, is a drug used to delay disease progression in adults suffering from transthyretin amyloidosis, and is marketed worldwide under different tradenames as a free acid or in the form of its meglumine salt. The free acid (CAS no. 594839-88-0) is reported to crystallize as distinct (polymorphic) crystal forms, the thermal stability and structural features of which remained thus far undisclosed. In this paper, we present—by selectively isolating highly pure batches of Tafamidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Artificial fingerprints made of oleic acid, squalene, jojoba oil, and corn oil consist of organic compounds. A carbon compound such as C=O, C=C, and CO bonds was suggested in previous studies [35,36]. In the case of the 2 wt% P25 coating layer, the characteristic peak representing the FT-IR spectrum was reduced after exposure to UV light for 20 min, indicating that CH (2674, 2925, 3006 cm −1 ), C=O (1743 cm −1 ), C=C (1655 cm −1 ), and CO (1170 cm −1 ) bonds decomposed under UV exposure.…”
Section: Resultsmentioning
confidence: 88%
“…Artificial fingerprints made of oleic acid, squalene, jojoba oil, and corn oil consist of organic compounds. A carbon compound such as C=O, C=C, and CO bonds was suggested in previous studies [35,36]. In the case of the 2 wt% P25 coating layer, the characteristic peak representing the FT-IR spectrum was reduced after exposure to UV light for 20 min, indicating that CH (2674, 2925, 3006 cm −1 ), C=O (1743 cm −1 ), C=C (1655 cm −1 ), and CO (1170 cm −1 ) bonds decomposed under UV exposure.…”
Section: Resultsmentioning
confidence: 88%
“…In the pharmaceutical field [11], these difficulties constitute a barrier to the physicochemical and pharmaceutical characterizations essential for the development of the active ingredients from different points of view. In-depth knowledge of the polymorphic behavior of an active ingredient, indeed, is essential for choosing the most suitable crystalline form for the formulation, avoiding unpleasant inconveniences due to the appearance of new crystalline forms in advanced stages of the development of a drug, guaranteeing its maintenance during manufacturing and storage, and defending the patent [12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphs are crystal forms composed of the same molecules with different molecular states due to changes in intermolecular interactions, resulting in changes in their physicochemical properties. Different molecular states among polymorphs can alter the physicochemical properties, which critically impact the in vivo performance of drugs, such as oral bioavailability. In addition, stability differences are particularly focused on in polymorphs, and metastable forms are often thermodynamically and kinetically transformed to a stable form with convergence to low free energy according to Ostwald’s rule of stages. Hence, revealing polymorphic forms and investigating their relationships are required for novel drug discovery. In the case of ritonavir, following its removal from the market, it was observed that the generation of a stable form during the manufacturing process reduced the dissolution rate and bioavailability of the drug. , Recent studies have found new polymorphic forms of traditional drugs, including ritonavir. From this viewpoint, polymorphs are considered regulatory…”
Section: Introductionmentioning
confidence: 99%